التنظيم القانوني لعقد القرض الدولي متعدد الأطراف - غريب، ابتهال حميد; البيضاني، فراس كريم شيعان (جامعة بابل - كلية القانون, 2021)
الأصل أن المقرض يقوم بتسليم مبلغ القرض إلى المقترض، ألا انه يحصل في بعض الأحيان قيام شخص ثالث بتسليم القرض إلى المقترض بناء على طلب المقرض أو وجود علاقة سابقة بينهما، فنكون في ذلك الفرض أمام عدة علاقات قانونية ودولية في ذات الوقت، التي تتمثل بالعلاقة بين المقرض المباشر والمقرض الغير المباشر والعلاقة بين المقرض الغير المباشر والمقترض. فضلا عن ذلك رغبة الأطراف في زيادة الأرباح يتطلب زيادة مبالغ الاقتراض التي تعجز بمفردها على تمويلها. فتلجا إلى الإقراض المشترك وعلية نكون أمام عقد القرض الدولي المجمع، الذي يكون بصورتين عن طريق تجمع المصارف أو بإصدار سندات القرض عن طريق الشركات نتيجة لتعدد الأطراف وتعارض المصالح. نتيجة لزيادة المبالغ في عقد القرض الدولي وتقلب الظروف تؤدي في بعض الأحيان إلى زعزعت الثقة بين الأطراف المتعاقدة، لذا تبرز أهمية تقديم الضمانات للمقرض التي تؤدي إلى استقرار وتشجيع على أبرام عقد القرض الدولي، تتمثل هذه الضمانات بالعينية والشخصية. لذا فإن تطبيق القانون الذي يحكم تلك العلاقات لا يخلو من صعوبة، سواء في ضل وجود الإرادة، أو غيابها.
The principle is that the lender delivers the loan amount to the borrower, but sometimes a third person delivers the loan to the borrower at the request of the lender or the existence of a previous relationship between them, so we are in that imposition in front of several legal and international relations at the same time, which is the relationship Between the direct lender and the indirect lender and the relationship between the indirect lender and the borrower. In addition, the parties ’desire to visit profits requires increasing the borrowing amounts that they alone are unable to finance. So resort to joint lending and therefore we are in front of the combined international loan contract, which is in two forms through a pool of banks or by issuing loan bonds through companies as a result of the multiplicity of parties and conflict of interests. As a result of the increase in the amounts in the international loan contract and the fluctuation of circumstances that sometimes lead to destabilizing the confidence between the contracting parties, so the importance of providing guarantees to the lender that leads to stability and encouragement for the conclusion of the international loan contract, these guarantees are in kind and in person. Therefore, the application of the law that governs these relationships is not without difficulty, whether in the presence of the will, or its absence.
Keywords: التنمية الاقتصادية -- القروض الدولية -- الضمانات العينية -- الأوراق التجارية -- القانون العراقي -- القانون الفرنسي